Fabrication and Characterization of Antibacterial and Biodegradable Facial Tissue Papers Using Bio-Based Raw Materials: Effect of Glycerin - Umaiya, Khandaker; Chowdhury, A.M. Sarwaruddin; Khan, Ruhul A. (Journal of Research Updates in Polymer Science, 2017)
Antibacterial facial tissue papers were prepared by solution casting method with chitosan loaded bleached cellulosic pulp. Chitosan, in the film act as an antibacterial agent. Tissue paper films were fabricated by 50% cellulose and 50% chitosan (by weight, dry basis). Mechanical properties of the films were evaluated. It was found that tensile strength (TS) and elongation at break (EB) of the 50% chitosan contain films were 24 MPa and 10.8% respectively. To increase the plasticity of the tissue paper films glycerin was added 0.4 to 2% (by weight). It was found that with the incorporation of 1% glycerin in the tissue paper films the flexibility increased to 50%. Molecular interaction due to the chitosan addition was investigated by Fourier Transform Infra-Red (FTIR) spectroscopy. Water uptake property of glycerin contains films were also evaluated. In the soil medium, the degradation properties of the tissue paper films were carried out. The antibacterial property of the tissue paper was evaluated by disk diffusion method.